Online search interest in the use of antibiotics for dental pain: an infodemiology study - Roxo-Gonçalves , Michelle; Valentim Bitencourt, Fernando; Britto Azevedo , Claudia; Fiorini , Tiago; Coelho Carrard , Vinicius (Brazilian Dental Science, 2022)
Objective: The objective of this study was to evaluate the online search interest pertaining to queries regardingantibiotics for dental pain. Material and Methods: Google Trends™ was used to identify the online searchinterest. Previously, a literature search was performed on the most frequently used antibiotics in dentistryin Brazil. Accordingly, the search terms used were Amoxicillin (AM), Clindamycin (CD), Azithromycin (AZ)and Metronidazole (MD), with the phrase “for toothache” in Portuguese and English. A time-series coveredthe last 240 weeks (from 2015 to 2020), and the results of each term were compared to their respectiveannual value. Geographic regions were also evaluated. To obtain a relative search volume (RSV), the resultingGoogle Trends™ numbers were then scaled to a range from 0 to 100 based on the ratio of searches on atopic to searches across all topics. Results: We observed an upward trend in all antibiotics search termsover the 5 years analyzed, with a peak of greater interest in 2019. The antibiotic of most interest related totoothache was ‘AM’, followed by ‘AZ’, ‘MD’, and ‘CD’. The annual RSV of toothache searches rose steadilyfrom 2015 to 2020. Variations were observed between Brazilian geographic regions, and the Northeastregion presented with the greatest interest in the topic. Conclusion: Although there were variations inannual and regional trends, an expressive and persistent increase in collective interest regarding the use ofantibiotics related to toothache, mainly amoxicillin, was observed. Our findings provide insights for publichealth promotion programs.KEYWORDSAntibiotics; Internet; Community pharmacies; Oral health; Public health.